Identificação de assédio moral em professores universitários - Teixeira, Nely Raquel Moroz (2014)
Workplace bullying is considered a type of psychological violence that affects companies in general and has been infecting and spreading among Higher Education institutions, damaging psycho-pedagogical and relational aspects in these organizations. This research aimed to verify the occurrence of workplace bullying in academic lecturers as well as identify the types of bullying suffered by them: by the employer or descending, among colleagues or horizontal and by the students or ascending. The sample comprised 285 professors (62%) from a Private College in the state of Paraná, Brazil. The participants answered a 10-question questionnaire, including 3 subscales, comprised of 50 items on workplace bullying practiced by the employer, colleagues and students. The research took place in the staff room and in the Postgraduate board room, before and between class periods. A descriptive statistical analysis (average, standard deviation, percentage) was conducted using the statistical software SPSS (Statistical Package for Social Sciences), the calculation of the Cronbach's alpha coefficient and ANOVA test. The total questionnaire had good indication of internal consistency ( = 0.931), as did the subscales of items relating to bullying by Employer (= 0.883), Colleagues ( = 0.874) and Students ( = 0.814). The results indicated that female participants were the major target of negative behaviors committed by the employer, colleagues and students. The average age of participants was 45,29 years (sd = 10,939), the minimum was 23 and the maximum was 77 years old. The percentage of workplace bullying experienced by the participants from employer was 13,2%, 12,2% from colleagues and 22,0% from students. Given the occurrence of negative acts, it is suggested that preventable interventions be made, aiming at informing on the topic, training in conflict resolution and in social skills, developing awareness campaigns and policies against workplace bullying in the university environment.